Localization of peroxidase activity in blood mononuclear phagocytes in pacu fish (Piaractus mesopotamicus) - Pellizzon, C. H. [UNESP]; Nakaghi, L. S O [UNESP]; Azevedo, A. [UNESP]; Casaletti, L.; Lunardi, L. O. (My University, 2002)
The localization of peroxidase activity in different cell regions is used as a criterion for classifying the stage of maturity of mammalian mononuclear phagocytes, with a positive peroxidase reaction indicating the presence of monoblasts, promonocytes, monocytes, and macrophages. Peroxidase activity was observed ultrastructurally in the circulating blood of pacu fish (Piaractus mesopotamicus), identifying monoblasts, promonocytes, monocytes, and macrophages. These observations suggest that differentiation of mononuclear phagocytes occurs in the blood circulation of fish, whereas in mammals, monoblasts and promonocytes are detected in bone marrow, with only monocytes detected in circulating blood and differentiation into macrophages occurring in other body compartments.
Keywords: Blood; Cellular maturation; Cytochemistry; Fish; Mononuclear phagocytes; Peroxidase activity; Piaractus mesopotamicus; peroxidase; animal cell; blood cell; cell differentiation; cell maturation; circulation; developmental stage; enzyme activity; enzyme localization; enzyme mechanism; fish; macrophage; male; mammal; monocyte; mononuclear phagocyte; nonhuman; observation; ultrastructure; animal; blood; chemistry; cytochemistry; electron microscopy; enzymology; metabolism; phagocytosis; physiology; Animalia; Mammalia; Piaractus; Animals; Cell Differentiation; Fishes; Histocytochemistry; Male; Microscopy, Electron; Monocytes; Peroxidase; Phagocytosis